Logística corporativa e territorialização do capital pelos lugares: análise da rede organizacional dos operadores logísticos vinculados ao Logproduzir de 2003 a 2015 - Bastos, Leila Sobreira (2016)
This work seeks to consider logistics as a fundamental attribute for corporate circulation and, consequently, for control, fluidity and territorial appropriation. We understand that logistics, more precisely the figure of the Logistic Operator, constitutes a fundamental agent capable of enhancing the use made to technical networks. In order to corroborate this idea, a study was made on logistics in the context of the expansion of capital with emphasis on Logistics Operators. In order to give depth to the discussion, our research object was the Logistic Operators benefited by the Produzir Program in Goiás. As result, we observed that, in Goiás, few companies can be considered, in fact, Logistics Operators, and among the companies benefited by the incentive towards the OLs, they are, in fact, carriers. In the same way, we observed that the truck drivers are central agents for the productive mobilization of the territory in Goiás and, nevertheless, the margin of the policies directed to the logistics is located, which represents a mistake, since this actor mobilizes a great part of the Agricultural production of the state and lack policies that provide productivity and quality at work. We tried to prove that the joint analysis of the State action and of a specific company format - Logistic Operator - contributes to the understanding of the Senses of modernization in Goiás. We believe that Logistical Operators are one of the new agents of modernity created to operationalize the fluidity and expansion of the contexts of modernity through the corporative apparatus of the territory. Keywords: Corporate Logistics, Logistic Operator, appropriation of technical networks, organizational network.